2018
DOI: 10.1002/2018pa003328
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Environmental Stress Delayed the Recovery of Marine Communities in the Aftermath of the Latest Permian Mass Extinction

Abstract: The aftermath of the latest Permian mass extinction is a key interval for the evolution of modern marine ecosystems. It has been hypothesized that the magnitude of the mass extinction delayed the subsequent recovery, and so to test this, we undertook the highest resolution study to date of the post‐extinction (Griesbachian) microbialite unit on the Great Bank of Guizhou, south China. The benthic community from the microbialite unit is taxonomically diverse when compared to other coeval deposits, recording both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 88 publications
4
27
0
Order By: Relevance
“…Studies of living microbialites have observed metazoans exploiting local oxygen refugia within the microbialites (e.g., Gingras, Lalond, Amskold, & Konhauser, 2007;Rishworth, Perissinotto, & Bird, 2016;Tarhan, Planavsky, Laumer, Stolz, & Reid, 2013). These metazoans, however, are typically softbodied, infaunal, and motile, which is not consistent with the epifaunal, stationary lifestyles of the benthic communities reported from the Great Bank of Guizhou (Foster et al, 2019). In addition, if the microbial mats were a preferable environment, we would expect that the microbial facies would contain a greater species richness and abundance than the surrounding non-microbial rocks, which was not observed in this study (Figures 4 and 5).…”
Section: Implications For Interpretation Of Oxygenated Environmentssupporting
confidence: 54%
See 3 more Smart Citations
“…Studies of living microbialites have observed metazoans exploiting local oxygen refugia within the microbialites (e.g., Gingras, Lalond, Amskold, & Konhauser, 2007;Rishworth, Perissinotto, & Bird, 2016;Tarhan, Planavsky, Laumer, Stolz, & Reid, 2013). These metazoans, however, are typically softbodied, infaunal, and motile, which is not consistent with the epifaunal, stationary lifestyles of the benthic communities reported from the Great Bank of Guizhou (Foster et al, 2019). In addition, if the microbial mats were a preferable environment, we would expect that the microbial facies would contain a greater species richness and abundance than the surrounding non-microbial rocks, which was not observed in this study (Figures 4 and 5).…”
Section: Implications For Interpretation Of Oxygenated Environmentssupporting
confidence: 54%
“…Nevertheless, the detailed investigation of this study records a greater diversity and abundance of fossils in the non‐microbial facies and non‐microbial fabrics found within the microbial facies than the microbial fabrics themselves (Figures and ). Furthermore, the microbialite samples investigated by (Foster, Lehrmann, et al., ) using the mechanical disaggregation method rarely yielded enough specimens (i.e., >50 specimens) for quantitative analysis. Most of the specimens within the microbialites are also disarticulated, and randomly orientated, and are thus inferred to have been transported into the microbialite framework (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all of the investigated localities, independent of region and stratigraphic level, the microbialites contain a high‐abundance assemblage of ostracods, microconchids, gastropods, bivalves and foraminifera, which have already been previously recognized (Baud et al , ; Forel et al , , ; Yang et al , ; Foster et al , ). These results show significant separation between the different investigated regions with the samples plotting into three main groups (Figure A).…”
Section: Faunal Composition Of Post‐extinction Microbialitesmentioning
confidence: 55%